Algal Biofilm and Phycoremediation - Güneş, K.; Özkan, Altan; Küçüker, Mehmet Ali; Kaplangı, B.B.; Özkan, A.; Kucuker, M.A. (CRC Press, 2024)
Various physical and chemical methods have been extensively studied and explored for the remediation of heavy metals, pesticides, and other contaminants present in wastewater. However, the chemicals used in these methods lead to a second treatment, causing problems such as high cost and application difficulties. To overcome this problem, the bioremediation method is an acceptable pollutant removal alternative. It is used as an efficient biological agent in bioremediation studies in microalgae and bacterial strains commonly used in treatment systems. Phycoremediation refers to microalgae-based pollutant removal. In recent studies with algal bioremediation, Chlorella sp., Scenedesmus sp., Spirulina platensis, and Chlamydomonas sp. have been used mostly to remove organic and inorganic pollutants from water streams. In this section, definitions regarding algal biofilm, including its formation mechanism and applications in remediation, will be provided. Subsequently, the suspended and attached algal growth systems commonly employed for pollutant removal will be studied. Furthermore, diverse methodologies utilized for the valorization of algal biomass will be examined. © 2025 selection and editorial matter, Maulin P. Shah and Günay Yıldız Töre.